Characterization and Neutron Shielding Behavior of Dehydrated Magnesium Borate Minerals Synthesized via Solid-State Method - Kipcak, Azmi Seyhun; Baysoy, Derya Yilmaz; Derun, Emek Moroydor; Piskin, Sabriye (HINDAWI LTD, 2013)
Magnesium borates are one of the major groups of boron minerals that have good neutron shielding performance. In this study, dehydrated magnesium borates were synthesized by solid-state method using magnesium oxide (MgO) and boron oxide (B2O3), in order to test their ability of neutron shielding. After synthesizing the dehydrated magnesium borates, characterizations were done by X-ray Diffraction (XRD), fourier transform infrared (FT-IR), Raman spectroscopy, and scanning electron microscopy (SEM). Also boron oxide (B2O3) contents and reaction yields (%) were calculated. XRD results showed that seven different types of dehydrated magnesium borates were synthesized. 1000 degrees C reaction temperature, 240 minutes of reaction time, and 3 : 2, 1 : 1 mole ratios of products were selected and tested for neutron transmission. Also reaction yields were calculated between 84 and 88% for the 3 : 2 mole ratio products. The neutron transmission experiments revealed that the 3 : 2 mole ratio of MgO to B2O3 neutron transmission results (0.618-0.655) was better than the ratio of 1 : 1 (0.772-0.843).
Keywords: MG2B2O5 NANOWIRES; Materials Science